Weight Suppression Predicts Bulimic Symptoms at 20-year Follow-up: The Mediating Role of Drive for Thinness - Bodell, Lindsay P. (J Abnorm Psychol, 2016)
Weight suppression predicts the onset and maintenance of bulimic syndromes. Despite this finding, no study has examined psychological mechanisms contributing to these associations using a longitudinal design. Given societal pressures to be thin and an actual history of higher weight, it is possible that greater weight suppression contributes to increased fear of gaining weight and preoccupation with being thin, which increase vulnerability to eating disorders. The present study investigated whether greater drive for thinness mediates associations between weight suppression and bulimic symptoms over long-term follow-up. Participants were women (n = 1190) and men (n = 509) who completed self-report surveys in college and 10- and 20- years later. Higher weight suppression at baseline predicted higher bulimic symptoms at 20-year follow-up (p < .001), while accounting for demographic variables and baseline bulimic symptoms, body mass index, and drive for thinness. Increased drive for thinness at 10-year follow-up mediated this effect. Findings highlight the long-lasting effect of weight suppression on bulimic symptoms and suggest that preoccupation with thinness may help maintain this association. Future studies would benefit from incorporating other hypothesized consequences of weight suppression, including biological factors, into risk models.